Filosofia em retomada: compreensão do projeto da filosofia com Éric Weil e Paul Ricoeur - Silva Júnior, Francisco Valdério Pereira da (2016)
This thesis addresses the relationship between Eric Weil and Paul Ricoeur. Despite being their styles fully different, at the treatment of philosophical questions, their perspectives converge in what we advocate here under the statute's project of philosophy - whether for a Logic of Philosophy (Weil), whether in a philosophical hermeneutics (Ricoeur). Weil and Ricoeur opt for this sense in any discourse, even in attempts to eliminate the sense, by attestation of indecision in view of the conflict of interpretations and / or of the impossibility of reducing violence to the speech. Neither the philosophy's logician, nor the hermeneut, it makes any concession to the easy reading of the multiplicity of discourses, trying to suppress them at a totalizing mediation. Nor they give in in to the powerful devastating criticism of the possibility of universalization that by supporting the radical polarization between every speech, consolidates fragmentation and permanent insuperability the deadlock environment. The resource that both throw hand is the resumption: concept able to operate a guidance through the discursive disparities in confrontation, respecting them the difference, while that rises beyond all fragmentation and incommunicability. Accepting the challenge of thinking about continuity, in spite of the ruptures in the history and discourse, they seek lead to reflection at the level of universal understanding by the possibility of coherent directioning, that is, judicious. In this sense, the thesis argues that the taking of Ricoeur's position is not only in favor of the weiliano philosophical project – synthesized in the Kantian formula post-Hegelian –, It is also the effective reappropriation of this active project, now, no longer by the chain of discursive typologies, but through the philosophical singularities